Environmental education in today's society: An experience in the school network (Research, Society and Development, 2019)
Environmental issues are often being discussed in society. The Environmental Education implemented in schools appears to be as an important educational tool, which seeks to raise awareness and stimulate the student to look around and feel an integral part of this environment, also contributing to the improvement of the quality of life, as well as the training of citizens aware. The BIOEDUCA project involved 55 students from the 2nd to 5th year of the Municipal School "Rosina Rodrigues Soares Silva" in the municipality of Barão de Cocais - MG. The environmental theme was approached in a dynamic and interactive way with the children, through lectures, group dynamics and practical activities aiming at the knowledge about the preservation of natural resources, the 3Rs and cycles of the materials. The students demonstrated interest and behavior change during the development of the work. The educational action demonstrated effectiveness in the transference of concepts about the environment and sustainability.